2022
DOI: 10.1177/23969873221078136
|View full text |Cite|
|
Sign up to set email alerts
|

Pressor therapy in acute ischaemic stroke: an updated systematic review

Abstract: Background Low blood pressure (BP) in acute ischaemic stroke (AIS) is associated with poor functional outcome, death, or severe disability. Increasing BP might benefit patients with post-stroke hypotension including those with potentially salvageable ischaemic penumbra. This updated systematic review considers the present evidence regarding the use of vasopressors in AIS. Methods We searched the Cochrane Database of Systematic Reviews, MEDLINE, EMBASE and trial databases using a structured search strategy. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 56 publications
(121 reference statements)
0
1
0
Order By: Relevance
“…Investigations into interventions to augment BP in the setting of acute ischemic stroke have not yielded clear BP targets, duration of therapy, or evidence of meaningful benefit. [36][37][38] Only a few studies thus far have demonstrated a potential role of induced hypertension in the treatment of acute stroke, particularly in patients who are not candidates for fibrinolytic or interventional therapies and with early neurologic deterioration. [39][40][41][42] For patients with fluctuating neurologic examinations or worsening deficits with drops in BP, volume expansion or pressure augmentation may be considered.…”
Section: Blood Pressure Managementmentioning
confidence: 99%
“…Investigations into interventions to augment BP in the setting of acute ischemic stroke have not yielded clear BP targets, duration of therapy, or evidence of meaningful benefit. [36][37][38] Only a few studies thus far have demonstrated a potential role of induced hypertension in the treatment of acute stroke, particularly in patients who are not candidates for fibrinolytic or interventional therapies and with early neurologic deterioration. [39][40][41][42] For patients with fluctuating neurologic examinations or worsening deficits with drops in BP, volume expansion or pressure augmentation may be considered.…”
Section: Blood Pressure Managementmentioning
confidence: 99%
“…Although a universally accepted definition of hypotension does not yet exist, brain perfusion is prioritised due to its high metabolic rate and lack of fuel storage, requiring a continuous supply of metabolic substrates and washing out of metabolic wastes via cerebral blood flow (CBF). Noradrenaline is one of the most commonly used vasopressors and is often a preferred choice for conditions including septic shock [1], traumatic brain injury [2], acute ischaemic stroke [3] and anaesthesia-related hypotension [4]. However, despite its widespread use, the effects of noradrenaline on CBF remain unresolved.…”
Section: Introductionmentioning
confidence: 99%